A study on 17alpha-ethinylestradiol metabolism in rat and Pleurotus ostreatus - Borek-Dohalska, Lucie; Valaskova, Petra; Kubickova, Bozena; Sulc, Miroslav; Kresinova, Zdena; Cajthaml, Tomas; Stiborova, Marie (Neuro-endocrinology letters, 2015)
OBJECTIVES: 17α-Ethinylestradiol (EE2) is an endocrine disruptor that is an ingredient of oral contraceptives. Here, EE2 metabolism catalyzed by cytochromes P450 (CYP) was studied. Two model organisms, rat and ligninolytic fungus Pleurotus ostreatus, were used. METHODS: To resolve the role of rat and/or fungal CYPs in EE2 oxidation, microsomes were incubated with EE2 and NADPH or cumene hydroperoxide. Using Supersomes™, we examined which of rat CYPs oxidize EE2. RESULTS: EE2 is effectively degraded by P. ostreatus in vivo. In vitro, EE2 is metabolized by CYPs by the NADPH-dependent and organic hydroperoxide-dependent mechanisms. Rat hepatic microsomes metabolize EE2 in the presence of NADPH to three products; two of them are hydroxylated EE2 derivatives. Using rat Supersomes™ we found that EE2 is hydroxylated by several rat CYPs, among them CYP2C6 and 2C11 are most efficient in 2-hydroxy-EE2 formation, while CYP2A and 3A catalyze EE2 hydroxylation to the second product. On the contrary, the products of the NADPH-dependent hydroxylating reactions were not detected in Pleurotus ostreatus. During the reaction of EE2 in microsomes isolated from rat and P. ostreatus in the presence of the alternate oxidant, cumene hydroperoxide, another metabolite, different from the above mentioned products, is generated. Rat CYP1A1 is the most efficient enzyme catalyzing formation of this EE2 product. CONCLUSION: The results suggest that CYPs play a role in EE2 metabolism in rat and P. ostreatus. To our knowledge this is the first finding describing ligninolythic fungal metabolism of EE2 by CYP in the presence of cumene hydroperoxide.
Keywords: Microsomes, Liver; cytochrom P-450 CYP3A; Male; steroid-16-alfa-hydroxylasa; steroid-21-hydroxylasa; Rats, Wistar; Hydroxylation; hydroxylace; vysokoúčinná kapalinová chromatografie; Cytochrome P-450 CYP1A1; Ethinyl Estradiol; cytochrom P-450 CYP1A1; mužské pohlaví; potkani Wistar; ethinylestradiol; Chromatography, High Pressure Liquid; Steroid Hydroxylases; oxidace-redukce; krysa rodu Rattus; systém (enzymů) cytochromů P-450; Animals; Pleurotus; aromatické hydroxylasy; Cytochrome P-450 Enzyme System; Cytochrome P-450 CYP3A; Aryl Hydrocarbon Hydroxylases; zvířata; Rats; Steroid 16-alpha-Hydroxylase; steroidhydroxylasy; Steroid 21-Hydroxylase; Oxidation-Reduction; jaterní mikrozomy